Manajemen Extrakurikuler Tahfiz Al-Qur’an Dalam Meningkatkan Prestasi Hafalan Siswa Di SMP Negeri 2 Bukittinggi - Salma Adilah; Fauzan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This thesis is entitled "Extracurricular Management of Tahfiz Al-Qur'an in Improving Students' Memorizing Achievement", written by Salma Adilah 2120319, Sjech M. Djamil Djambek Bukittinggi, Faculty of Tarbiyah and Teacher Training, State Islamic University (UIN) - Islamic Religious Education Study Program This research is motivated by the extracurricular management of tahfiz Al-Qur'an at SMP Negeri 2 Bukittinggi. In theory, SMP is related to the issue of tahfiz Al-Qur'an in general it is not specifically regulated, usually those involved in the field of tahfiz are children of Islamic boarding schools, religious schools (Mts) and but the reality is that at SMP Negeri 2 Bukittinggi there is a lot of memorization. A good management process is really needed in the extracurricular activities of tahfiz Al-Qur'an at SMP Negeri 2 Bukittinggi so that memorization achievement can increase. The focus of this research is related to (planning, organizing, implementing and supervising). The method used in this research is descriptive qualitative, namely describing a situation or event that occurs in the field. Data collection techniques use observation, interviews and documentation techniques. Data analysis techniques use data observation techniques, data and presentation, and conclusions. Data validity uses source triangulation and time triangulation. The informants in this research were the chairman of the core management as the key informant, and the supporting informants were the core administrators of Al-Qur'an tahfiz and students of SMP Negeri 2 Bukittinggi. The objects in this research are students who take part in the extracurricular tahfiz Al-Qur'an. The research results are: first, Planning, the planning function is oriented towards goal-based planning. Second, organizing: 1Division of administrative responsibilities and work using a departmental method based on function. 2) Systems theory is the extra organizing theory that is applied. 3. Choosing and hiring management personnel carry out a deliberation and consensus system (the process of discussing issues together in order to reach a mutual agreement). Third, actuating (implementation), namely 1), leadership style theory, namely supportive theory. 2), the nature and type of leadership used by the missionary type (leadership assignment). 3), memorization method. Fourth, controlling (supervision) uses a type of supervision based on evaluation.